Constantly low‐phase‐noise differential VCO based on balanced tunable quasi‐elliptic and constant‐ABW BPF. Issue 5 (19th February 2021) - Li, Zhiyou; Tang, Xiaohong; Liu, Yong; Lu, Di; Cai, Zongqi
Abstract: In this article, a parallel‐feedback differential voltage‐controlled oscillator (VCO) with constantly low‐phase noise and frequency tuning range (FTR) of 1.72–2.12 GHz (20.8%) is presented. The presented differential VCO with differential outputs and low‐phase noise is achieved using a four‐pole tunable balanced bandpass filter (BAL‐BPF) with quasi‐elliptic frequency response as a frequency stabilization element. The low‐phase noise is obtained and maintained because of the high in‐band group delay and the constant absolute bandwidth (CABW) of the used tunable BAL‐BPF. For demonstration, an example is designed, fabricated, and measured. The measured oscillation frequency of the differential VCO can be tuned from 1.72–2.12 GHz (20.8%) and the phase noises keep better than −99 dBc/Hz @100 kHz and − 129.1 dBc/Hz @1 MHz over the FTR. In the meantime, the differential oscillating signals are generated at two outputs.